Measuring the dielectric and optical response of millimeter-scale amorphous and hexagonal boron nitride films grown on epitaxial graphene. (13th December 2017) - Rigosi, Albert F; Hill, Heather M; Glavin, Nicholas R; Pookpanratana, Sujitra J; Yang, Yanfei; Boosalis, Alexander G; Hu, Jiuning; Rice, Anthony; Allerman, Andrew A; Nguyen, Nhan V; Hacker, Christina A; Elmquist, Randolph E; et al.
Abstract: Monolayer epitaxial graphene (EG), grown on the Si face of SiC, is an advantageous material for a variety of electronic and optical applications. EG forms as a single crystal over millimeter-scale areas and consequently, the large scale single crystal can be utilized as a template for growth of other materials. In this work, we present the use of EG as a template to form millimeter-scale amorphous and hexagonal boron nitride ( a -BN and h -BN) films. The a -BN is formed with pulsed laser deposition and the h -BN is grown with triethylboron (TEB) and NH3 precursors, making it the first metal organic chemical vapor deposition (MOCVD) process of this growth type performed on epitaxial graphene. A variety of optical and non-optical characterization methods are used to determine the optical absorption and dielectric functions of the EG, a -BN, and h -BN within the energy range of 1 eV–8.5 eV. Furthermore, we report the first ellipsometric observation of high-energy resonant excitons in EG from the 4H polytype of SiC and an analysis on the interactions within the EG and h -BN heterostructure.